2020
DOI: 10.1101/2020.12.28.424535
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitrononalcoholic fatty liver disease model with cyclo-olefin-polymer-based microphysiological systems

Abstract: Nonalcoholic fatty liver disease (NAFLD) is one of the common chronic liver conditions, whose treatment involves curing patients without liver transplantation. Understanding the mechanism of NAFLD initiation and progression would enable development of new diagnostic tools and drugs; however, until now, the underlying mechanisms of this condition remain largely unknown owing to the lack of experimental settings that can simplify the complicated NAFLD process in vitro. Microphysiological systems (MPSs) have long… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Rennet et al reported a human liver model in a COC-based system with microfluidic flow conditions to study the influence of sepsis (severe inflammation) on hepatocellular dysfunction [ 9 ]. Wen et al modeled a nonalcoholic fatty liver disease model with a cyclo-olefin polymer-based device seeded with a HepaRG hepatoma cell line [ 11 ]. Reported platforms have all been made solely of COC.…”
Section: Introductionmentioning
confidence: 99%
“…Rennet et al reported a human liver model in a COC-based system with microfluidic flow conditions to study the influence of sepsis (severe inflammation) on hepatocellular dysfunction [ 9 ]. Wen et al modeled a nonalcoholic fatty liver disease model with a cyclo-olefin polymer-based device seeded with a HepaRG hepatoma cell line [ 11 ]. Reported platforms have all been made solely of COC.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, COC-based devices are also used to study illicit drug analysis and DNA amplification by performing a chip multiple displacement amplification reaction . Similarly, Wen et al demonstrated the use of COP for modeling a nonalcoholic fatty liver disease microphysiological system . The majority of microfluidic devices fabricated in laboratories required expensive equipment, which becomes difficult for all institutions to afford.…”
Section: Ooc Materialsmentioning
confidence: 99%
“…Kamei et al developed a NAFLD model using a chip made of cyclo-olefin polymer (COP). 115 Hepatocytes were cultured on a chip made of PDMS and a chip made of COP, and the adsorption of AdipoRed lipid dye was compared. It was observed that the adsorption of lipid dyes was lower in the COP material.…”
Section: Liver Disease Modelsmentioning
confidence: 99%